COMPARATIVE ANALYSIS OF THE PRINCIPLES OF CROSS-BORDER INSOLVENCY - Grigoryan, Gohar (State and Law, 2023)
The article is devoted to the principles and methods of cross-border insolvency. The article reveals the peculiarities, as well as the advantages and disadvantages of the two main methods of cross-border insolvency (territoriality and universalism). Moreover, the article presents the main provisions of legal documents adopted by famous international organizations about territoriality and universalism, and respective conclusions are made.
Keywords: cross-border insolvency; principle; universalism; territorialism; creditor; debtor; foreign